Adenoid Cystic Carcinoma of the Breast in a Male Patient: A Case Report and Literature Review - Wan, Dan; Zhou, Hongyuan; Zhang, Yutao (Frontiers in Oncology, 2022)
Adenoid cystic carcinoma (ACC) of the breast (breast ACC) is a rare tumor, especially in men, with only 17 cases reported in the literature. Owing to this rarity, male breast ACC is susceptible to missed or incorrect diagnoses, and data on treatment options and prognosis is also scarce. Herein, we report a case of a male patient with primary breast ACC and performed a detailed clinicopathological analysis of the 17 cases reported in the literature. A 38-year-old Chinese man patient developed right-sided breast nipple retraction in 2013 and presented to our hospital in 2015 with a palpable mass in the right breast for four days. B-scan ultrasound indicated the presence of a solid space-occupying lesion in the right breast. Breast Imaging Reporting and Data System (BI-RADS) classified the lesion as category 4B, and mammography showed a right breast nodule classified as BI-RADS 4C. Modified radical mastectomy for breast cancer was performed on the right breast. Microscopic examination of the excised tissue revealed diffuse tumor invasion of the subcutaneous fibers and adipose tissue, with tumor cells arranged in cribriform, tubular, and microcystic patterns. Immunohistochemical staining indicated that the glandular epithelial cells were positive for CD117, CK7, and Ki67 (approximately 30%) and negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2, while the myoepithelial cells were positive for P63, CK5/6 and S-100. Moreover, basement membrane materials were positive for collagen type IV. Molecular pathology analysis by fluorescence in situ hybridization revealed that the tumor was negative for MYB rearrangements. The patient was followed up for 82 months with no tumor recurrence or metastasis. According to the current literature, mastectomies have a better prognosis than lumpectomy. Accurately identifying the diagnosis of male breast ACC and considering the surgery of mastectomy may be the key factors for patients to obtain a good prognosis based on the microscopic characteristics of the tumor.